Metastatik meme kanseri tedavisinde lapatinib kapesitabin kombinasyonun etkinliğinin retrospektif değerlendirilmesi - Çubukçu, Erdem; Ocak, Birol; Ölmez, Ömer Fatih; Deligönül, Adem; Kaçan, Turgut (My University, 2019)
Tüm dünyada meme kanseri kadınlarda kanserin ve kanser ilişkili ölümlerin en sık nedenidir. Meme kanserli hastaların %17-30 HER2overekspresyonu olup hastalık, kötü prognoz, hastalık progresyon riskinde artış, genel sağkalım ve progresyona kadar geçen sürenin herikisinde azalma ile birliktedir. Lapatinib, HER2 ve epidermal büyüme faktör reseptör(EGFR) ün ilk dual tirozin kinaz inhibitörüdür. Buçalışma da antrasiklin, taksan ve trastuzumab tedavisi sonrasında progrese olan metastatik meme kanserli hastalarda kapesitabin ve lapatinibkombinasyonunun etkisini ve tolerabilitesini inceledik. Medyan yaş 56 (34-76) olan toplam 24 hasta dosyası Eylül 2010-Mayıs 2018 arasında3 merkezde retrospektif olarak incelendi. Tüm hastalar taksan ve antrasiklin içeren kemoterapi ve trastuzumab sonrası progrese olanHER2 pozitif metastatik meme kanseri hastalardı. Genel cevap oranı %29.1, 2 komplet yanıt (CR, 8.3%), 5 parsiyel yanıt (PR, 20.8%) ve 7stabil hastalık (SD, 29.1%) olmak üzere sağlandı. Kapesitabin ve lapatinib kombinasyon tedavisi antrasiklin, taksan ve trastuzumab tedavisisonrasında progrese olan metastatik meme kanserli hastalarda etkili ve iyi tolere edilmiştir.

Worldwide, breast cancer is the most common malignancy and cause of cancer-related death in women. In the 17%–30% of breast cancer patients who overexpress ErbB2 (HER2), the disease is associated with poorer prognosis, greater risk for disease progression and reductions in both progression free survival (PFS) and overall survival (OS). Lapatinib is the first dual tyrosine kinase inhibitor of human epidermal growth factor receptor type 2 (HER2/neu) and epidermal growth factor receptor (EGFR). The present study evaluated the efficacy and tolerability of the combination of lapatinib and capecitabine in patients with metastatic breast cancer (MBC) who progressed after therapy with trastuzumab, a taxane and/or anthracycline. A total of 24 patients with a median age of 56 (34-76) were evaluated retrospectively in 3 centers between September 2010 and May 2018. All the patients had HER2 positive MBC progressing after trastuzumab and chemotherapy including an anthracycline and/or taxane. An overall response rate (ORR) of 29.1% was achieved including 2 complete responses (CR, 8.3%), 5 partial responses (PR, 20.8%), and 7 stable disease (SD, 29.1%). Lapatinib and capecitabine combination therapy is effective and well tolerated in patients with MBC who had progressive disease after trastuzumab, taxane, and/or anthracycline therapy.
Retrospective evaluation of the efficacy of lapatinib capecitabine in the treatment of metastatic breast cancer
Keywords: Meme Kanseri; Metastatik Meme Kanseri; Retrospektif; Breast Cancer; Metastatic Breast Cancer; Retrospective